Dermatological Presentations in Systemic Lupus Erythematosus: A Comprehensive Case Study - Earlia, Nanda; Salim, Fitria; Hidayati, Arie; Pradistha, Aldilla; Ibrahim, Teuku Maulana Malik; Azzahra, Shelda Syifa; Maulidina, Rizka Yuliani (Indonesian Journal of Case Reports, 2024)
Lupus erythematosus (LE) is an inflammatory autoimmune disease with a broad clinical spectrum of multi-organ inflammation and can be life-threatening. Manifestations of LE can occur confined to the skin (cutaneous lupus erythematosus, CLE) or systemic involving several organs such as the kidneys, heart, and lungs (systemic lupus erythematosus, SLE). We report a female, 27-year-old with complaints of black spots on her back, stomach area, hands, and feet. The patient feels that the spots increase when doing activities outside the home. Patients also complain of fever, pain when swallowing, joint pain, fatigue, and hair loss. Dermatological status in the abdominal, posterior thoracic, and extremities regions shows the presence of macules accompanied by hyperpigmented patches with unclear borders, irregular edges, gutta-plaque size, multiple numbers, and atypical arrangement and configuration. In the ANA profile examination, the native SS-A antigen (60 kDa) +++ results were strongly positive. The examination results concluded CLE type Subacute CLE (SCLE). The patient was given Calcium Carbonate capsules, Folic Acid tablets, and Methylprednisolone tablets. Topical medications include tretinoin 0.25% cream, momethasone 0.1% cream, Desoximethasone 0.25% cream, clobetasol propional 0.05% cream, and must use Sunscreen morning and evening. After 2 weeks, the patient showed good results. The black spots are starting to fade. Other complaints, such as fever, fatigue, and pain when swallowing, have decreased. Cutaneous lupus can be a challenge to treat because the symptoms are varied and complex. Management of CLE aims to eliminate symptoms and signs of the disease, prevent damage from occurring, minimize side effects of drugs, and improve quality of life.